2013
DOI: 10.4049/jimmunol.1300521
|View full text |Cite
|
Sign up to set email alerts
|

Complete TCR-α Gene Locus Control Region Activity in T Cells Derived In Vitro from Embryonic Stem Cells

Abstract: Locus Control Regions (LCR) are cis-acting gene regulatory elements with the unique, integration site-independent ability to transfer the characteristics of their locus-of-origin’s gene expression pattern to a linked transgene in mice. LCR activities have been discovered in numerous T cell lineage expressed gene loci. These elements can be adapted to the design of stem cell gene therapy vectors that direct robust therapeutic gene expression to the T cell progeny of engineered stem cells. Currently, transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 60 publications
(81 reference statements)
3
12
0
Order By: Relevance
“…Analogous to the results seen for the β-globin LCR, we have reported that the TCRα LCR cannot drive transgene expression in a copy number-dependent manner after its direct introduction into differentiated T cells (Lahiji et al, 2013). This is in stark contrast to the activity of identical TCRα LCR-driven reporter constructs in transgenic mice, within which all the hallmarks of TCRα LCR activity are consistently observed (Harrow and Ortiz, 2005; Knirr et al, 2010).…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…Analogous to the results seen for the β-globin LCR, we have reported that the TCRα LCR cannot drive transgene expression in a copy number-dependent manner after its direct introduction into differentiated T cells (Lahiji et al, 2013). This is in stark contrast to the activity of identical TCRα LCR-driven reporter constructs in transgenic mice, within which all the hallmarks of TCRα LCR activity are consistently observed (Harrow and Ortiz, 2005; Knirr et al, 2010).…”
Section: Introductionsupporting
confidence: 66%
“…Since the estimated number of integrated transgene copies in these clones (3 and 5) are within a range that yields copy number-dependent expression (Lahiji et al, 2013), this apparent silencing is not due to excessive transgene copy number. Thus, it seems that transfected ESCs will be less hospitable to the function to YFP, and perhaps any non-mammalian reporter cDNA, during differentiation than are standard cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ES cells (34). Hence, features of the hCD2 reporter dictate the developmental profile of Tcra LCR-hCD2 activity.…”
Section: Discussionmentioning
confidence: 99%